First national rolling plan.(1990-92) - Nigeria. Federal Ministry of Budget and Planning; Nigeria, Federal Republic (Lagos : Planning Office, Federal Ministry of Budget and Planning, 1990)
This is the first three-year national rolling plan referred to as the economic consolidation and expansion programme aimed at consolidating the gains of the Structural Adjustment Programme and pursuing sustainable growth through the 90s for the management of the economy.
oif 10/04/2019
Nigeriana
Keywords: Economic policy; Social policy; Economic planning; Nigeria